2024
DOI: 10.3390/coatings14020218
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of TiO2 Nanoparticles on the Physico–Mechanical and Structural Characteristics of Cementitious Materials

Carmen T. Florean,
Horatiu Vermesan,
Gyorgy Thalmaier
et al.

Abstract: The urgent need for sustainable construction that corresponds to the three pillars of sustainable development is obvious and continuously requires innovative solutions. Cementitious composites with TiO2 nanoparticles (NT) addition show potential due to their improved durability, physico–mechanical characteristics, and self-cleaning capacity. This study aimed to evaluate the influence of NT on cementitious composites by comparing those with 2%–5% nanoparticles with a similar control sample without nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…As can be seen in Figure 8, the inclusion of NT in the composite matrix resulted in an increased degree of whiteness in the composite surfaces compared to the analogous sample prepared without NT for all types of aggregates. This behaviour was anticipated based on references in the literature [52,54], highlighting the use of TiO 2 as a whitening agent for a wide range of materials, from paints to products in the cosmetics and pharmaceutical industries. Although the amount of NT used as an additive was the same for all compositions (3% by weight relative to the amount of cement, the amount of cement being kept constant), it was observed that the increase in the degree of whiteness was influenced by the type of aggregates derived from waste that replaced NA, ranging from 4.89% for GBA to 14.04% for RTA.…”
Section: Analysis Of the Self-cleaning Properties Of Cementitious Com...mentioning
confidence: 78%
See 1 more Smart Citation
“…As can be seen in Figure 8, the inclusion of NT in the composite matrix resulted in an increased degree of whiteness in the composite surfaces compared to the analogous sample prepared without NT for all types of aggregates. This behaviour was anticipated based on references in the literature [52,54], highlighting the use of TiO 2 as a whitening agent for a wide range of materials, from paints to products in the cosmetics and pharmaceutical industries. Although the amount of NT used as an additive was the same for all compositions (3% by weight relative to the amount of cement, the amount of cement being kept constant), it was observed that the increase in the degree of whiteness was influenced by the type of aggregates derived from waste that replaced NA, ranging from 4.89% for GBA to 14.04% for RTA.…”
Section: Analysis Of the Self-cleaning Properties Of Cementitious Com...mentioning
confidence: 78%
“…based on the amount of cement) (R5-3NT). The proportions of natural aggregates replaced by recycled waste aggregates and the addition of 3% TiO2 nanoparticles (by weight relative to the amount of cement) were determined based on preliminary research [52][53][54]. This research evaluated the influence of these two factors on the physico-mechanical properties and durability of the cementitious composites.…”
mentioning
confidence: 99%
“…The first is the difficulty of achieving a uniform distribution of nano-and micro-sized photocatalysts in the concrete mixture [16]. The second is the reduction in the physico-mechanical characteristics of concrete products at high doses of the photocatalyst in their composition [17]. The third is the reduction in the efficiency of photocatalysts when they are mixed with concrete components owing to a decrease in the amount of absorbed light (inhibition of photon transport) and the free surface (inhibition of diffusion of reagents) for photocatalytic reactions [18].…”
Section: Introductionmentioning
confidence: 99%